PEMBUATAN VIDEO DOKUMENTER DAMPAK PENGGUNAAN BILINGUAL PADA ANAK USIA DINI - Daniel Nugroho Josoputro; Monica Widiasri; Fransisca Liliana (Perpustakaan Universitas Surabaya, 2018)
Abstract - A lot of parents prepare their children in fulfilling their need of the era of globalization by learning foreign languages at an early age. There are many differences of opinion whether bilingual is best applied in early childhood. From the analysis, it was found that the information on the effect of bilingual at an early age that exist on the media website is difficult to understand and its content unreliable by parents of young children. Therefore, they invented a video documentary on the effect of the use of bilingual early childhood that is easily understood and trusted by parents of young children.